Isolation, characterization and the multi-lineage differentiation potential of rabbit bone marrow-derived mesenchymal stem cells - Tan, S.L.; Ahmad, T.S.; Selvaratnam, L.; Kamarul, Tunku (2013)
Mesenchymal stem cells (MSCs) are recognized by their plastic adherent ability, fibroblastic-like appearance, expression of specific surface protein markers, and are defined by their ability to undergo multi-lineage differentiation. Although rabbit bone marrow-derived MSCs (rbMSCs) have been used extensively in previous studies especially in translational research, these cells have neither been defined morphologically and ultrastructurally, nor been compared with their counterparts in humans in their multi-lineage differentiation ability. A study was therefore conducted to define the morphology, surface marker proteins, ultrastructure and multi-lineage differentiation ability of rbMSCs. Herein, the primary rbMSC cultures of three adult New Zealand white rabbits (at least 4 months old) were used for three independent experiments. rbMSCs were isolated using the gradient-centrifugation method, an established technique for human MSCs (hMSCs) isolation. Cells were characterized by phase contrast microscopy observation, transmission electron microscopy analysis, reverse transcriptase-polymerase chain reaction (PCR) analysis, immunocytochemistry staining, flow cytometry, alamarBlueÂ® assay, histological staining and quantitative (q)PCR analysis. The isolated plastic adherent cells were in fibroblastic spindle-shape and possessed eccentric, irregular-shaped nuclei as well as rich inner cytoplasmic zones similar to that of hMSCs. The rbMSCs expressed CD29, CD44, CD73, CD81, CD90 and CD166, but were negative (or dim positive) for CD34, CD45, CD117 and HLD-DR. Despite having similar morphology and phenotypic expression, rbMSCs possessed significantly larger cell size but had a lower proliferation rate as compared with hMSCs. Using established protocols to differentiate hMSCs, rbMSCs underwent osteogenic, adipogenic and chondrogenic differentiation. Interestingly, differentiated rbMSCs demonstrated higher levels of osteogenic (Runx2) and chondrogenic (Sox9) gene expressions than that of hMSCs (P<0.05). There was, however, no difference in the adipogenic (Pparγ) expressions between these cell types (P>0.05). rbMSCs possess similar morphological characteristics to hMSCs, but have a higher potential for osteogenic and chondrogenic differentiation, despite having a lower cell proliferation rate than hMSCs. The characteristics reported here may be used as a comprehensive set of criteria to define or characterize rbMSCs.